Terapia ocupacional, território e comunidade: desvelando teorias e práticas a partir de um diálogo latino-americano - Bianchi, Pamela Cristina (Universidade Federal de São Carlos, 2019)
The present study aimed to know the territorial and community actions in Latin America, using a dialectical historical materialist reading. The terms territory and community fit into the political, economic and social relations established in the capitalist model of production. In occupational therapy, the terms were incorporated as a result of political, social and economic events in the countries, as a way to unite criticism about social reality with professional practices. The study aimed to understand the theoretical and conceptual development of the terms territory and community and its reflection on the practical actions performed by occupational therapy in Argentina, Brazil, Chile and Colombia. To this end, data collection was performed in two stages: in the first, we elaborated four conceptual reviews of the literature, including eight interviews with most recurrent authors in the analyzed references of each country; in the second stage, social case studies were conducted through four participant observations, including interviews with the social actors present in the experiences followed. The results on the conceptual development identified that the productions of Brazil and Colombia presented concepts to the term territory, since community is more used in the Argentine and Chilean productions. In Argentina, the use of the term community and community actions began in the 1980s, influenced by the country's economic and political crises. In Brazil, community was incorporated by political militancy of professionals in the late 1970s, while territory entered the field amid psychiatric reform and the advancement of public policies in the 1990s; territorial and community action circumscribes collective micro-level interventions that seek to produce resonances in the social macrostructure. In Chile, community is incorporated in the early 1970s, composing the movement for democracy in the country, while territory was already used in the 1990s with the implementation of public policies; in practice, the actions correspond to community work, aimed at strengthening people's social participation. In Colombia, the use of the term community began in the 1980s as a result of the work of professionals with the victims of an environmental catastrophe and in university extension projects, territory started to be used after the implementation of territorial public policies and strengthened with Peace Agreement in 2016; territorial and community actions are correlated with social vulnerability and situations of violence. In the case studies, five principles present in the territorial-community action in Latin American occupational therapy stand out: the action implied in the collective and in social relations; the weaving of formal and informal networks; the building of bonds through the use of activities; the horizontality and availability in relationships; and strategies to address social vulnerability at the micro and macrosocial scopes. Finally, we indicate that the territory concept suggests a combination of space, process and relationship, surpassing the definition of a physical geographic space. While community brings the idea of collectivity, networks, belonging and identity. It is concluded that both are used in an articulated manner, which presupposes a reflection on people's ways of life and the relationships they establish with their living spaces in search of an intervention that promotes the weaving of solidarity in places as one of the purposes of the technical action.
Terapia ocupacional, território y comunidad: desvelando teorias e prácticas desde um diálogo latinoamericano
Keywords: Terapia ocupacional; América latina; Formação de conceito; Território; Comunidade; Vulnerabilidade social; Formación de conceptos; Territorio; Comunidad; Vulnerabilidad social; Occupational therapy; Latin America; Concept formation; Territory; Community; Social vulnerability; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL